Discriminatory Practices against Women in Labour Relations in Nigeria: Interrogating the Position of International Law - Atah Pine; Ochoga Edwin Ochoga (International Studies Journal)
Previous studies mainly focused on the discrimination against women in Nigerian society (including labour relations) without emphasis to the position of international law, and international law is the global norm. This is the gap that this paper seeks to fill in literature regarding discriminatory practices against women in labour relations in Nigeria. The paper adopts face-to-face interview as an instrument of data collection to get opinion of some expertise on gender and international law with a triangulation of secondary sources of information. The paper adopts interrogative technique of qualitative data analysis and argued that International Labour Organization’s Declaration on Fundamental Principles and Right; and the 1979 United Nations Convention on the Elimination of all forms Discrimination Against Women are legal instruments of international law against discrimination of women in labour relations. It is upon these global legal norms that the Nigeria Constitution and the Nigerian Labour Act derived it principles from. It is revealed that the discrimination against women in labour relation is grounded in unwritten Conventions, religion and tradition of the working places. Employer-employee relation is clearly defined under the international law which is in line with the Nigerian Labour Law. Therefore, any contractual agreement aims at discriminating workers on the basis of their sex amount to an aberrational act. The paper has equally discovered that the fear of losing one’s job often makes women to work under any condition whatsoever which is different from the position of international law. The paper has recommended that the rights and privileges provided under the Labour Act are balanced to all citizens and as such, the onus lies in the hands of women themselves to fight against discrimination at work place